1987
DOI: 10.1007/bf02013018
|View full text |Cite
|
Sign up to set email alerts
|

Surface attachment of nitrifying bacteria and their inhibition by potassium ethyl xanthate

Abstract: Ion exchange resins and glass microscope slides were used to investigate factors affecting attachment of nitrifying bacteria to solid surfaces and the effect of attachment on inhibition ofNitrobacter by potassium ethyl xanthate. The ammonium oxidizerNitrosomonas attached preferentially to cation exchange resins while the nitrite oxidizerNitrobacter colonized anion exchange resins more extensively. Colonization was always associated with growth, and the site of substrate (NH4 (+) or NO2 (-)) adsorption was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…It is the fate of this NO 2 ( pool that determines the NO flux. Underhill & Prosser (1987) showed that Nitrosomonas, which oxidise NH 3 to NO 2 ( , and Nitrobacter, Multiple regression non-significant B0.01 Non-significant 7.6…”
Section: Discussionmentioning
confidence: 98%
“…It is the fate of this NO 2 ( pool that determines the NO flux. Underhill & Prosser (1987) showed that Nitrosomonas, which oxidise NH 3 to NO 2 ( , and Nitrobacter, Multiple regression non-significant B0.01 Non-significant 7.6…”
Section: Discussionmentioning
confidence: 98%
“…Sullivan & Palmisano (1984) concluded that ca 30 % of the ice bacteria in McMurdo Sound were attached to living algae or associated detritus. Although these authors did not identify the attached organisms or measure their activity, laboratory studies have shown that nitrifying bacteria (both NH: oxidizers and NO; oxidizers) grow better when attached to surfaces (Underhill & Prosser 1987, Diab & Shilo 1988, Keen & Prosser 1988. Diab & Shilo found that the nitrifylng bacterial genera Nitrosornonas and Nitrobacter rapidly attached to a number of different surfaces which resulted in enhanced activity of attached bacteria relative to freely suspended cells.…”
Section: Discussionmentioning
confidence: 99%
“…The first reported observation of this effect was made in 1943, where it was found that bacterial activity increased in the presence of glass surfaces, particularly with low nutrient concentrations (54). Since this first study, researchers have examined how various materials, including glass and polymer surfaces (10, 11, 24-26, 40, 44, 47), silicone surfaces (52), ceramic surfaces (32), dialysis membranes (18), activated carbon (7), clays (43), sands (31,48), estuary particles (19), and ion exchange resins (46), affect the metabolic activity of attached bacteria.…”
mentioning
confidence: 99%